Student Perceptions of Online Learning in Pencak Silat Courses During The Covid-19 Pandemic - Citra Azhariat Malasari; Guntur Yulisatria (Universitas PGRI Palembang, 2023)
This study aims to determine students' perceptions of online learning in martial arts courses during the covuid-19 pandemic. This type of research is a quantitative descriptive research with research instruments in the form of questionnaires that are distributed directly with data collection methods using the Likert scale. Sampling uses the total sampling technique, namely all 24 students who have taken martial arts courses in the class of 2020. The results showed that the questionnaire of student responses to learning from is included in the good category based on the results of student responses to online learning using the WhatsApp application in the good category with an answer average respondents of 65.33%, using the Zoom Cloud Meeting application in the category is not good with the answer average respondents of 62.58%, using the SiAkad Cloud application in the good category with the answer average respondents by 63.08%, using the Edlink application in the good category with an average answer of 63.29%.